How Blue Was My Valley? Invited Paper for the AERA Special Interest Group on Rural Education - Craig B. Howley; Aimee Howley (Journal of Research in Rural Education, 2018)
Did rural America1 bring Donald Trump to the presidency? The New York Times, the Washington Post, and the Atlantic Monthly say so (see, e.g., Brownstein, 2016; Quirk, 2016). And it's an undeniable fact that 62% of small town and rural voters cast ballots for Trump (Morin, 2016)